FENOMENA KEKUASAAN POLITIK DAN EKSISTENSI GENDER DALAM PERKEMBANGAN PENDIDIKAN - M Zaki` (Sophist : Jurnal Sosial Politik Kajian Islam dan Tafsir, 2018)
The link between education and politics is understood by the community in two ways. First there are community groups who say that education is education and politics is political or between the two is separate. Secondly there are groups of people who argue that the two are interrelated. in a narrow sense, it needs to be remembered that politics in the narrow sense is interpreted as part of society as a politics of national life in which there is competition between certain groups or groups to fight for a desired position or position by justifying any means. Politics in education actually exists, an example; a vocational school principal who decides the policy of apprenticeship patterns for his students, whether that decision cannot be considered a political decision. Another example is the regulations concerning education that the government decides in the form of policies or guidelines are actually political decisions as well